The prognosis impact of hyperthermic intraperitoneal chemotherapy (HIPEC) plus cytoreductive surgery (CRS) in advanced ovarian cancer: the meta-analysis - Zhang, Guyu (J Ovarian Res, 2019)
BACKGROUND AND OBJECTIVE: Previous studies about the prognostic value of the HIPEC have yielded controversial results. Therefore, this study aims to assess the impact of HIPEC on patients with ovarian cancer. RESULTS: We included 13 comparative studies, and found that the overall survival (OS) and progression-free survival (PFS) in HIPEC groups were superior to groups without HIPEC treatment in the all total population (HR = 0.54,95% CI:0.45 to 0.66, HR = 0.45, 95% CI: 0.32 to 0.62). Additionally, the subgroup analysis showed that patients with advanced primary ovarian cancers also gained improved OS and PFS benefit from HIPEC (HR = 0.59,95% CI:0.46 to 0.75, HR = 0.41,95% CI:0.32 to 0.54). With regard to recurrent ovarian cancer, HIPEC was associated with improved OS (HR = 0.45,95% CI:0.24 to 0.83), but for the PFS, no correlation was observed between HIPC group and the non-HIPEC group (HR = 0.55,95% CI:0.27 to 1.11). HIPEC also led to favorable clinical outcome (HR = 0.64,95% CI:0.50 to 0.82, HR = 0.36,95% CI:0.20 to 0.65) for stage III or IV ovarian cancer with initial diagnosis. CONCLUSION: The review indicated that HIPEC-based regimens was correlated with better clinical prognosis for patients with primary ovarian cancers. For recurrent ovarian cancers, HIPEC only improved the OS but did not elicit significant value on the PFS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13048-019-0509-1) contains supplementary material, which is available to authorized users.